67.7k views
10 votes
3(x-4)=2(-2x+1) what does x equal

User YMH
by
5.0k points

2 Answers

6 votes

Answer: 2=x

Explanation:

3(x-4)=2(-2x+1) <- multiply number outside of parentheses by numbers inside parentheses

1)3x-12=-4x+2

2)-3x -3x <- subtract -3x

-12=-7x+2 <- what you should have after

3)-2 -2 <- subtract 2

-14=-7x <- what you should have after

4)/-7 /-7 <- divide by -7

2=x <- what you should have after

/= divide

remember: negative multiplied by a negative equals a positive, and a negative multiplied by a positive equals a negative.

User Andrea Di Giorgi
by
4.4k points
2 votes

Answer:

x = 2

Explanation:

Given

3(x - 4) = 2(- 2x + 1) ← distribute parenthesis on both sides

3x - 12 = - 4x + 2 ( add 4x to both sides )

7x - 12 = 2 ( add 12 to both sides )

7x = 14 ( divide both sides by 7 )

x = 2

User Chrisntr
by
4.9k points